The Maintenance Of The Sasak Language In The Samawa Speech Community: A Case Study Of Karang Anyar - Eki Hizbi Ramadhan; Kamaluddin Yusra; Jaswadi Putera (Jurnal Inovasi Global, 2025)
This study examines factors affecting the maintenance of the Sasak language in Karang Anyar amid increasing multilingualism. Understanding these factors is vital for its survival against the dominance of Indonesian and other regional languages. The focus is on the meno-mene dialect spoken in Karang Anyar Hamlet. Employing a qualitative method, data was collected through observations, interviews, and recordings to analyze the natural use of the Sasak language in daily life. The study highlights social, cultural, and linguistic elements influencing language maintenance, involving various community members from different generations. Data analysis through transcription and classification revealed strong daily use of the Sasak language. The community exhibits multilingual skills, switching among Sasak, Indonesian, and Sumbawa. Factors sustaining this include social, demographic, economic, cultural, family, and attitudinal influences, while political and educational ones are less significant. Although residents preserve the Sasak language well, a dedicated institution is needed to ensure its future preservation and prevent extinction.